Physicochemical characteristics and functionality of tree peony (Paeonia suffruticosa Andr.) seed protein. (1st February 2018) - Gao, Lei-Lei; Li, Ying-Qiu; Wang, Zhao-Sheng; Sun, Gui-Jin; Qi, Xiang-Ming; Mo, Hai-Zhen
Highlights: The protein 60 kDa of tree peony seed protein had two subunits of 38 and 23 kDa. Two subunits with pI 3.6 and 9.0 contained all three types. Tree peony seed protein had a favourable amino acid profile. Tree peony seed protein had a predominantly β-sheet structure and was heat stable. TPSP was a pseudoplastic fluid with desirable functional properties. Abstract: The physicochemical and functional properties of tree peony seed protein were investigated. Tree peony seed protein with a favourable amino acid profile was composed of a 60 kDa protein with two subunits of 38 and 23 kDa. The isoelectric points of the two subunits were 3.6 and 9.0. Moreover, acid-Schiff staining indicated both of them were glycoproteins. Diagonal and 2-D electrophoresis data indicated the 38 kDa subunit included three types, which two types had inter-disulphide bonds and one type had no-disulphide bonds. So did the 23 kDa subunit. Circular dichroism spectra indicated the tree peony seed protein had predominantly a β-sheet structure. Differential scanning calorimetry analysis indicated the denaturation temperatures of the tree peony seed protein at pH 5.0, 7.0 and 9.0 were 92.0, 97.1 and 95.2 °C, respectively. Tree peony seed protein could be a food ingredient in the food industry due to its desirable physicochemical and functional properties.